Strengthening the Market of Bathok Koi Coconut Shell Waste Crafts through Digital Marketing System in Achieving Brand Awareness - Wardani, Shanti Ike; Widayani, Anna; Fu’ad, M. Nur; Waspada, Heri Priya (Pascasarjana Universitas Mataram, 2024)
This research aims to increase brand awareness and competitiveness of Bathok Koi coconut shell waste handicraft products through the implementation of digital marketing strategies. The program involved intensive training for micro business partners and university students, covering digital marketing skills such as social media management, product photography, and creative content creation for digital platforms. The results of the program showed an increase in participants' understanding of branding and digital marketing which resulted in increased interactions with consumers and increased visits to Bathok Koi's social media profiles. In conclusion, continuous assistance in digital marketing is needed to encourage business sustainability and strengthen Bathok Koi's position in local and regional markets